2014
DOI: 10.3390/toxins6020509
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Patterns in Cyanobacteria Distribution: Climate Influence at Regional Scale

Abstract: Cyanobacteria are a component of public health hazards in freshwater environments because of their potential as toxin producers. Eutrophication has long been considered the main cause of cyanobacteria outbreak and proliferation, whereas many studies emphasized the effect of abiotic parameters (mainly temperature and light) on cell growth rate or toxin production. In view of the growing concerns of global change consequences on public health parameters, this study attempts to enlighten climate influence on cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…In temperate eutrophic freshwaters, Microcystis and Planktothrix may co‐occur, with Planktothrix being an early colonizer and Microcystis appearing subsequently (Engelke et al ., ; Jang et al ., ; Pitois et al ., ; Reichswaldt et al ., ; Guellati et al ., ). In a previous laboratory study, Engelke and colleagues () reported an increase of MC concentrations in M. aeruginosa PCC 7820 cells in response to the presence of the non‐MC‐producing P. agardhii CYA 29 or its spent medium, and that this interaction led to an inhibition of P. agardhii growth.…”
Section: Introductionmentioning
confidence: 99%
“…In temperate eutrophic freshwaters, Microcystis and Planktothrix may co‐occur, with Planktothrix being an early colonizer and Microcystis appearing subsequently (Engelke et al ., ; Jang et al ., ; Pitois et al ., ; Reichswaldt et al ., ; Guellati et al ., ). In a previous laboratory study, Engelke and colleagues () reported an increase of MC concentrations in M. aeruginosa PCC 7820 cells in response to the presence of the non‐MC‐producing P. agardhii CYA 29 or its spent medium, and that this interaction led to an inhibition of P. agardhii growth.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant blooming genus in the upstream freshwater reservoir was overwhelmingly Microcystis, consistent with the most widespread cyanobacterial occurrence of Microcystis in freshwaters worldwide (Harke et al, 2016) and as well as in Brittany (Pitois et al, 2014). While cyanobacterial transfer from freshwaters to estuaries has been reported for around 20 years, the majority of studies worldwide reported that M. aeruginosa was the dominant species transferred to coastal waters (Preece et al, 2017 for a review).…”
Section: Discussionmentioning
confidence: 54%
“…The toxicity of Microcystis is also known to vary among species, M. wesenbergii being rarely found toxic, while the majority of M. aeruginosa and M. viridis is reported as toxic (Harke et al, 2016, Otten et al, 2017. The MC concentration in the reservoir and the estuary was most likely due to Microcystis sp., due to its overwhelming dominance and the high percentage of potentially toxic species within that genus in Brittany (Pitois et al, 2014). P. agardhii is also known to produce MCs in relatively large quantities (Briand et al, 2009;Lance et al, 2007) and the most toxic bloom reported in Italy's estuarine waters was indeed one of Planktothrix (De Pace et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcystin-LR (MC-LR) that is secreted from M. aeruginosa is known to be hepatotoxic and cause neural toxicity (Bhattacharya et al, 1996;Ekvall et al, 2014a;Ekvall et al, 2014b;Lone et al, 2015;Pitois et al, 2014;Shen et al, 2003;Yoshida et al, 1997). Chronic oral administration of MC-LR to rats was reported to induce the impairment of spatial learning and memory, inflammatory response by astrocyte activation, and liver dysfunction (Li et al, 2014a;Li et al, 2014b;Yoshida et al, 1997).…”
Section: Introductionmentioning
confidence: 99%